Management of Late Descemet's Membrane Detachment after Penetrating Keratoplasty in Keratoconus - Weller, Julia; Kruse, Friedrich; Schlötzer-Schrehardt, Ursula; Tourtas, Theofilos (Cornea, 2022)
Purpose:The purpose of this study was to describe the feasibility of Descemet membrane endothelial keratoplasty (DMEK) as a treatment modality for spontaneous detachment of DM (DMD) decades after penetrating keratoplasty (PK) for keratoconus.Methods:We describe the clinical characteristics and therapeutic surgical approach in 6 eyes of 5 patients with DMD. Clinical images, anterior segment optical coherence tomography scans, and histological findings are presented.Results:Mean age of patients at time of diagnosis was 60 years (range 56-66 years). Mean interval between PK and occurrence of DM detachment was 36 years (range 29-45 years). In 4 of 6 eyes, air injections into the anterior chamber were initially attempted to reattach DM to the stroma but without long-lasting effect. Two eyes underwent repeat PK because of pronounced ectasia after long-standing DMD and stromal scars. DMEK was performed successfully in 4 eyes leading to an increase in visual acuity and a reduction in central corneal thickness. Electron microscopy showed abnormal vacuolar inclusions and collagenous material in the posterior nonbanded layer and a separation of the anterior banded layer from the posterior nonbanded layer.Conclusions:This case series provides evidence that DMEK is a viable option in eyes with spontaneous DM detachment after PK. Visual outcome is limited by the persisting high astigmatism in the ectatic cornea. Illustrated by a small series of patients, the results of DMEK in this condition are presented and new findings about the pathophysiology are given.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Descemet membrane detachment; DMEK; keratoconus